The Third Industrial Revolution: Policymaking for the Internet - Smith, Bradford (Science and Technology Law Review, 2019)
The Internet heralds the onset of a third industrial revolution, one based in technological advances in software, hardware and telecommunications. These technological advances are transforming commercial practices, generating substantial gains in productivity and opening new avenues for political and social expression. But like the industrial revolutions that preceded it, the Internet revolution raises difficult legal and social issues, which in turn have generated a growing body of laws and regulatory proposals. This article seeks to provide an analytic structure for addressing and resolving the legal and policy challenges raised by the Internet. It endorses the use of self-regulatory and other extra-legal solutions to these challenges, but argues that governments should establish a supportive regulatory framework and should ensure that proposed solutions ultimately represent the public interest. This approach also seeks to look beyond traditional notions of the public and private sectors’ respective roles and to articulate a model that harnesses each sector’s unique strengths and abilities in reaching viable, practical solutions to online problems. Four themes form the cornerstones of this approach: (1) liberal use of market-based solutions; (2) reliance on technology solutions for problems rooted in technology; (3) recognition of government’s multi-faceted role in responding to online challenges; and (4) support for broader international harmonization of applicable rules. This article also examines two prominent schools of legal scholarship in this area and argues that, while each provides valuable insights into law’s relationship to the Internet, neither position offers a compelling response to key online legal and policy issues.